Preparation of trinucleotide phosphoramidites as synthons for the synthesis of gene libraries - Suchsland, Ruth; Appel, Bettina; Müller, Sabine (Beilstein Journal of Organic Chemistry, 2018)
The preparation of protein libraries is a key issue in protein engineering and biotechnology. Such libraries can be prepared by a variety of methods, starting from the respective gene library. The challenge in gene library preparation is to achieve controlled total or partial randomization at any predefined number and position of codons of a given gene, in order to obtain a library with a maximum number of potentially successful candidates. This purpose is best achieved by the usage of trinucleotide synthons for codon-based gene synthesis. We here review the strategies for the preparation of fully protected trinucleotides, emphasizing more recent developments for their synthesis on solid phase and on soluble polymers, and their use as synthons in standard DNA synthesis.
Keywords: gene library; protein engineering; soluble support; synthesis; trinucleotide